2016
DOI: 10.1016/j.elecom.2016.07.011
|View full text |Cite
|
Sign up to set email alerts
|

Poly(anthraquinonyl sulfide) cathode for potassium-ion batteries

Abstract: Potassium-ion batteries (KIBs) are a promising sustainable energy storage technology due to the high abundance and low cost of potassium. Carbon anode materials for KIBs have seen great successes, but the development of cathode materials is yet to catch up. In this study, poly(anthraquinonyl sulfide) (PAQS) is evaluated as a cathode material for KIBs. It exhibits a high reversible capacity of 200 mAh/g, which is the highest value for a potassium storage cathode material. The cell shows two slopes averaged at 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
182
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 249 publications
(187 citation statements)
references
References 22 publications
5
182
0
Order By: Relevance
“…[104] However, ex situ XRD and infrared spectroscopy indicate that the structural evolution upon K insertion and extraction is irreversible, suggesting possible parasitic contributions to the capacity. K storage in poly(anthraquinonyl) sulfide (PAQS) was also demonstrated by Jian et al [105] One PAQS molecule was observed to uptake two K ions upon discharge (211 mA h g −1 at 20 mA g −1 in 1.5-3.4 V) when using 0.5 m KTFSI in mixed dimethoxyethane and dioxolane solution (1:1 ratio by volume). Zhao et al showed that oxocarbon (C 6 O 6 ) can cycle two K ions in the voltage range of 1-3.2 V, delivering a capacity of 212 mA h g −1 at 0.2 C. [90] These authors also compared the kinetics of K storage in the oxocarbon with that for Li and Na and found that the K diffusivity estimated by cyclic voltammetry is higher than those of Li and Na for the same system.…”
Section: Organic Cathodesmentioning
confidence: 89%
See 1 more Smart Citation
“…[104] However, ex situ XRD and infrared spectroscopy indicate that the structural evolution upon K insertion and extraction is irreversible, suggesting possible parasitic contributions to the capacity. K storage in poly(anthraquinonyl) sulfide (PAQS) was also demonstrated by Jian et al [105] One PAQS molecule was observed to uptake two K ions upon discharge (211 mA h g −1 at 20 mA g −1 in 1.5-3.4 V) when using 0.5 m KTFSI in mixed dimethoxyethane and dioxolane solution (1:1 ratio by volume). Zhao et al showed that oxocarbon (C 6 O 6 ) can cycle two K ions in the voltage range of 1-3.2 V, delivering a capacity of 212 mA h g −1 at 0.2 C. [90] These authors also compared the kinetics of K storage in the oxocarbon with that for Li and Na and found that the K diffusivity estimated by cyclic voltammetry is higher than those of Li and Na for the same system.…”
Section: Organic Cathodesmentioning
confidence: 89%
“…[104,105] Using 3,4,9,10-perylene-tetracarboxylic acid-dianhydride as a K storage host, they reported a capacity of 129 mA h g −1 for the first discharge at 20 mA g −1 in the voltage range of 1.2-3.2 V with 0.8 m KPF 6 in EC:DEC with a 1:1 ratio by volume. [104] However, ex situ XRD and infrared spectroscopy indicate that the structural evolution upon K insertion and extraction is irreversible, suggesting possible parasitic contributions to the capacity.…”
Section: Organic Cathodesmentioning
confidence: 99%
“…[5] Later, the amorphous phase of FePO 4 as well as organic materials were also suggested as cathodes for KIBs. [6][7][8][9] Recently, K-ion insertion was shown to be possible in K 0.3 MnO 2 , [21] but the low K content of that material requires the use of K metal or pre-potassiated anodes.…”
Section: Doi: 101002/aenm201700098mentioning
confidence: 99%
“…[3] This interesting feature suggests that KIBs might potentially deliver a higher cell voltage than Na-ion batteries (NIBs) and even LIBs. In addition, K-ion technology would benefit from the fact that graphite can be used on the anode side [3,4] (as in Li ion), which is not the case for Na ion and has seriously limited application of Na-ion technology.Only a few cathode compounds have been reported to date for KIBs, [5][6][7][8][9] with most studies focusing on the development of anodes. [3,4,[10][11][12][13][14][15][16][17][18][19][20] For example, Eftekhari demonstrated that Prussian blue can reversibly store K ions in a nonaqueous electrolyte system.…”
mentioning
confidence: 99%
See 1 more Smart Citation